2016
DOI: 10.1002/pros.23174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel androgen receptor transgene responsive to MicroRNA mediated post-transcriptional control exerted via 3′-untranslated region

Abstract: AR transgenes with AR 3'-UTR fragments closely resemble the endogenous AR expression than any other previously characterized AR expression constructs. The 3'-UTR containing AR expression system is amiable to post-transcriptional manipulations including miRNA mediated repression of AR expression. This AR reporter system has the potential to be used in determining specificity of AR targeting miRNAs and their role in AR functional regulatory networks. Prostate 76:834-844, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Hence, the expression of miR-101 changes upon androgen treatment. Ebron & Shukla (2016) also found that overexpression of miR-488 mimics can repress the expression of reporters containing the 3′-UTR of AR. It has to be noted that miR-221 and miR-222 are oncogenic miRNAs as well, which are overexpressed in cancers, such as breast, pancreas, liver, and lung cancer.…”
Section: Androgen Receptormentioning
confidence: 89%
See 1 more Smart Citation
“…Hence, the expression of miR-101 changes upon androgen treatment. Ebron & Shukla (2016) also found that overexpression of miR-488 mimics can repress the expression of reporters containing the 3′-UTR of AR. It has to be noted that miR-221 and miR-222 are oncogenic miRNAs as well, which are overexpressed in cancers, such as breast, pancreas, liver, and lung cancer.…”
Section: Androgen Receptormentioning
confidence: 89%
“…This variant is a result of a "gain of function" mutation and a potential mechanism of the resistance development to second-generation AR antagonists, such as abiraterone and enzalutamide. Accordingly, AR-related miRNAs could have a role in drug resistance in PCa (Table 1; Ebron & Shukla, 2016). For example, miR-1 is known as a tumor suppressor and a regulator of metastatic PCa.…”
Section: Androgen Receptormentioning
confidence: 99%
“…13,14 Certain miRNAs have been shown to regulate tumor progression via binding to the AR 3ʹ-UTR sequence. [15][16][17] As the expression of miRNAs is associated with HCC progression and metastasis, [18][19][20] and AR might promote HCC cell proliferation, it would be interesting to determine if miRNAs serve as AR upstream regulators to alter HCC cell proliferation. Bioinformatic analyses from literature and online databases (TargetScan, miRDB, and MicroCosm Targets) suggest that a subset of miRNAs, including miR-99b-5p, miR-101-3p, miR-135b-5p, miR-373-3p, and miR-375, may target the AR 3ʹ-UTR sequence and simultaneously inhibit HCC progression.…”
Section: Introductionmentioning
confidence: 99%